Analyzing the Impact of Service Delivery, Pricing, and Facilities on Customer Satisfaction at Big Mart: A Descriptive and Causal-Comparative Study - Rayamajhi, Aayusha; Sejuwal, Narendra (International Journal of Atharva, 2024)
This study investigates customer satisfaction at Big Mart, focusing on service delivery, pricing, and facilities. Utilizing a descriptive and causal-comparative research design, data was collected from 125 customers in the Baluwatar area, employing a questionnaire and convenient sampling technique. The research explores the relationship between service delivery, pricing, facilities, and customer satisfaction. Descriptive statistics reveal average satisfaction with service delivery and pricing, but notable dissatisfaction with facilities. Correlation analysis indicates significant positive correlations between service delivery and pricing, while other facilities negatively affect satisfaction. Regression analysis shows that 28.6 percent of the variance in customer satisfaction is explained by the model, with price positively impacting satisfaction and other facilities having a significant negative effect. The findings suggest that enhancing facility quality and maintaining competitive pricing are crucial for improving overall customer satisfaction at Big Mart.